2009
DOI: 10.2519/jospt.2009.2932
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Patellofemoral Articular Cartilage Wear in Cadavers

Abstract: Anatomical studies describe the structure of the articulating bones, the articular cartilage, and the lack of joint congruity. 7,12,17,44,[50][51][52] The triangular patella has a rounded superior pole and a pointed inferior pole (FiGUre 1). Anteriorly, its surface is embedded in the quadriceps tendon. Posteriorly, its surface articulates with t STUdY deSiGn: Descriptive.t oBJeCTiVe: Describe and compare patellar and femoral condylar wear patterns, and the wear frequency of both, relative to each other, gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…The gender effect on kneeling ability is an important observation but inconclusive because of a relatively small number of patients involved. According to Gorniak et al the pattern of RPC wears was more central and compact in males than in females (gender difference in wear area) [15]. This gender difference both in wear area noticed by Gorniak et al and the observed kneeling ability differences may also relate to males usually ability before TKA.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The gender effect on kneeling ability is an important observation but inconclusive because of a relatively small number of patients involved. According to Gorniak et al the pattern of RPC wears was more central and compact in males than in females (gender difference in wear area) [15]. This gender difference both in wear area noticed by Gorniak et al and the observed kneeling ability differences may also relate to males usually ability before TKA.…”
Section: Discussionmentioning
confidence: 84%
“…A study performed by Gorniak et al to detect any common specific-joint wear pattern at the patellofemoral joint in 26 cadavers (50 patellae) from older individuals [15]. The study found that there is greater medial patellar facet and odd facet wear than lateral facet wears, suggesting higher medial than lateral patellofemoral joint contact forces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the main clinical concern has been that patients with PFPS experience a higher load in the lateral facet of the PF joint. But, interestingly, a few recent studies have shown evidence of pain and cartilage wear in the medial side of the PF joints as well as medial shift of the patella (Gorniak 2009;Song et al 2011;Draper et al 2012). These findings have constituted a clear contradiction of the previous reports discussing the PFPS, in which most of the research focused on the lateral aspect (lateral malalignment/ maltracking) of the PF joints as a sole contributor of PFPS.…”
Section: Introductionmentioning
confidence: 96%